Prevalence and antimicrobial resistance of Enterococcus spp. isolated from animal feed in Japan - Yamagami, Yohei; Asao, Miyuki; Takahashi, Akiko; Hashimoto, Yoshiyasu; Okuyama, Noriko; Arai, Eiko; Arihara, Wakana; Masui, Ryota; Shimazaki, Yoko (Frontiers in Veterinary Science, 2024)
The rising prevalence of antimicrobial resistance (AMR) of bacteria is a global health problem at the human, animal, and environmental interfaces, which necessitates the “One Health” approach. AMR of bacteria in animal feed are a potential cause of the prevalence in livestock; however, the role remains unclear. To date, there is limited research on AMR of bacteria in animal feed in Japan. In this study, a total of 57 complete feed samples and 275 feed ingredient samples were collected between 2018–2020. Enterococcus spp. were present in 82.5% of complete feed (47/57 samples), 76.5% of soybean meal (62/81), 49.6% of fish meal (55/111), 33.3% of poultry meal (22/66), and 47.1% of meat and bone meal (8/17) samples. Of 295 isolates, E. faecium (33.2% of total isolates) was the dominant Enterococcus spp., followed by E. faecalis (14.2%), E. hirae (6.4%), E. durans (2.7%), E. casseliflavus (2.4%), and E. gallinarum (1.0%). Of 134 isolates which were tested for antimicrobial susceptibility, resistance to kanamycin was the highest (26.1%), followed by erythromycin (24.6%), tetracycline (6.0%), lincomycin (2.2%), tylosin (1.5%), gentamicin (0.8%), and ciprofloxacin (0.8%). All Enterococcus spp. exhibited susceptibility to ampicillin, vancomycin, and chloramphenicol. Of 33 erythromycin-resistant isolates, only two showed a high minimum inhibitory concentration value (>128 μg/mL) and possessed ermB. These results revealed that overall resistance to antimicrobials is relatively low; however, animal feed is a source of Enterococcus spp. It is essential to elucidate the causative factors related to the prevalence of AMR in animal feed.